Civil protection and the risk of the use of weapons of mass destruction: actualization of the use of dual-purpose shelters in Serbia (International Journal of Contemporary Security Studies, 2024)
The special military operation that the Russian Federation launched on the territory of Ukraine on February 24, 2022, brings with it a number of problematic issues not only from the domain of military sciences but now increasingly specific security sciences (energy security, environmental security, food security, health security).